ANALISIS KESALAHAN PESERTA DIDIK KELAS XI MIA SMA NEGERI 1 PAINAN BERDASARKAN TAHAPAN KASTOLAN DALAM MENYELESAIKAN SOAL MATEMATIKA - Firli . (Jurnal Edukasi dan Penelitian Matematika, 2021)
Student error analysis is an important thing to find out student mastery. It turned out that errors were found by students of class XI MIA SMA Negeri 1 Painan in solving polynomial math problems. The purpose of this study is to identify student errors and factors that cause these errors. This type of research is descriptive research with a qualitative research approach. The data in this study are data from observations, tests, and interviews. The data was analyzed using qualitative analysis techniques, namely data reduction, data display, and conclusion. Based on the results of the research, the errors made by students include: 1) conceptual error of 30.8%, students cannot define polynomial forms and determine polynomial degrees, 2) procedural error of 42.3%, students wrong in determining the steps to solve problems, 3) technical error of 26, 9%, students make mistakes in accuracy and wrong in calculating the value of arithmetic operations. Keywords — error analysis, kastolan.